1985
DOI: 10.1111/j.1547-5069.1985.tb01631.x
|View full text |Cite
|
Sign up to set email alerts
|

The Participant Philosophy in Nursing Science

Abstract: The central thesis of this article is that scientific rigor is necessary but not sufkient to address the broad human issues that challenge the nursing profssion. The pursuit of scientific rigor has led nurse researchers away from personal engagement in the issues they wish to study. Clinical scholarship demands active engagement in the practice arena. Three modes of knowledge acquisition-quantitative, qualitative, and personal-are identified and discussed in the context of Pirsig's (1974) "participant philosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Expansion needs to occur not only within nursing but also beyond our disciplinary borders. There is a growing recognition among nurse researchers of the importance of multiple theoretical perspectives and pluralistic methodologies in building our knowledge base (Bargagliotti, 1983;Goodwin & Goodwin, 1984;Silva & Rothbart, 1984;Smith, 1984;Tilden & Tilden, 1985), and family nurse scientists have much to gain from the experience of others working on similar questions from different viewpoints.…”
Section: "Family" In Nursing Sciencementioning
confidence: 99%
“…Expansion needs to occur not only within nursing but also beyond our disciplinary borders. There is a growing recognition among nurse researchers of the importance of multiple theoretical perspectives and pluralistic methodologies in building our knowledge base (Bargagliotti, 1983;Goodwin & Goodwin, 1984;Silva & Rothbart, 1984;Smith, 1984;Tilden & Tilden, 1985), and family nurse scientists have much to gain from the experience of others working on similar questions from different viewpoints.…”
Section: "Family" In Nursing Sciencementioning
confidence: 99%
“…In agreement, Beck (1994b, 500) declares that ‘[t]he use of self as a data collection instrument’ in phenomenology is similar to the nurse’s ‘therapeutic use of self’. Her view resonates with the belief that phenomenology entails personal knowledge (Tilden and Tilden 1985) obtained by personal engagement in nursing practice (Taylor 1993).…”
Section: Nursing’s Appeal To Phenomenologymentioning
confidence: 70%
“…Since the heart of phenomenological theory and methodology focuses on the problem of intersubjectivity (Anderson 1989), rather than either subjects or objects (Munhall and Oiler 1986), phenomenology affords insights into the nurse–patient ‘I‐Thou encounter’ (Pallikkathayil and Morgan 1991) to discover ways of caring (Theobald 1997). Thus, not only is phenomenological philosophy congruent with nursing philosophy (Rose et al 1995), but clinical nursing skills coextend with the phenomenologist’s skills to ‘study actors in the field’ (Tilden and Tilden 1985, 3–4). In summary, phenomenology has the potential to reveal ‘humanistic and nursing‐humanistic values in relation to nursing phenomena’ (Ray 1985, 85).…”
Section: Phenomenology In Nursing As a Humanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown, Tanner, and Padrick (1984) concluded that this need is the result of a shift from the goal of description to that of explanation in nursing research. Others stated that the need for more sophisticated and pluralistic methods is due to changing philosophical trends both in science and nursing (Tilden & Tilden, 1985;Allen, 1985;Leininger, 1985;Silva & Rothbart, 1984;Sarter, 1987;Thompson, 1983Thompson, , 1985Thompson, , 1987. Still others stated that the need for more sophisticated methods of inquiry is related to the progress nursing is making in its development as a discipline.…”
mentioning
confidence: 99%